Study of Antibacterial Activities of Seeds Extract of Fenugreek (Trigonella foenum-graecum) - Alhan M Alwan; Izdehar M Jassim; Ghssan M Jasim (Diyala Journal of Medicine, 2018)
Background: The antibacterial activity of seeds  methanol extract and hot aqueous extract  of fenugreek (Trigonella foenum-graecum) showed the  presence of  activity  against four species of bacteria and the methanol extract have higher activity than other extract.